2007
DOI: 10.1308/003588407x205468
|View full text |Cite
|
Sign up to set email alerts
|

The Ultimate Aberdeen Knot

Abstract: An Aberdeen knot tied with three throws and two turns is the ultimate Aberdeen knot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 1 publication
4
30
0
Order By: Relevance
“…In our study, we tested varying number of throws in large gauge suture and showed that there was no significant difference in the KHC and RKS as the number of throws increased when comparing knots of the same suture material. These results are again similar to that of a previous study investigating the Aberdeen knot, where it was reported there was no additional benefit to placing >3 throws using 0 polydioxanone . Given the data obtained, it is recommended to place at least 3 throws when tying forwarder knots in large gauge (2 and 3 USP), and a fourth throw can be placed to ensure that maximum KHC is achieved.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, we tested varying number of throws in large gauge suture and showed that there was no significant difference in the KHC and RKS as the number of throws increased when comparing knots of the same suture material. These results are again similar to that of a previous study investigating the Aberdeen knot, where it was reported there was no additional benefit to placing >3 throws using 0 polydioxanone . Given the data obtained, it is recommended to place at least 3 throws when tying forwarder knots in large gauge (2 and 3 USP), and a fourth throw can be placed to ensure that maximum KHC is achieved.…”
Section: Discussionsupporting
confidence: 86%
“…Even though some papers have claimed to have found objective evidence for an optimum knot [22], the issue remains controversial and the search for the perfect knot continues [10,[23][24][25][26][27]. As the results reported in the literature are not standardized and not easily comparable [28], the technique options presented tend to confuse rather than help the surgical community [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…cannot be answered conclusively [25]. On the one hand, in view of the fact that foreign bodies such as sutures induce an inflammatory response [42], it is reasonable to use as few knots as possible.…”
Section: Introductionmentioning
confidence: 99%
“…The Aberdeen knot has long been demonstrated to be a strong and secure method for ending a suture line [9]. It is designed not to be undone and, therefore, does not have an inbuilt mechanism to be untied [10]. We describe a simple and practical way of incorporating the Aberdeen knot to close wounds using the subcuticular stitch.…”
Section: Introductionmentioning
confidence: 99%